Systemic effects of vibration under conditions of long-term bed rest: A Systematic Review - Gializi, Athanasia; Kalyviotis, Marios; Nanas, Serafeim; Philippou, Anastassios; Vasileiadis, Ioannis (Health & Research Journal, 2025)
Background: Prolonged bed rest induces significant dysfunction across multiple physiological systems that can surpass normal aging. Whole-body vibration (WBV) has been proposed as a non-pharmacological countermeasure, yet its systemic impact remains inadequately investigated Objective: This systematic review aimed to explore the effects of WBV under conditions of prolonged immobilization, not only on the musculoskeletal system but also on the endocrine, vascular, and metabolic systems. Particular attention was given to whether WBV alone can elicit systemic responses beyond the site of application. Methods: Following PRISMA guidelines, literature was searched in PubMed, Cochrane, and Greynet until February 2024. Seventeen studies met the inclusion criteria. Methodological quality was assessed using the PEDro scale. Data extraction focused on vibration protocols, physiological outcomes, and the presence or absence of concomitant exercise. Results: WBV demonstrated protective effects on muscle morphology, function, and contractility, as well as bone remodeling and mineral density. Favorable alterations were also reported in endocrine, metabolic, and vascular parameters. However, in most studies, WBV was combined with resistance exercises, limiting conclusions about its independent systemic action. Passive WBV protocols in healthy and critically ill individuals showed localized effects near the application site, but systemic extrapolation remains inconclusive. Conclusions: WBV may confer multi-systemic benefits during prolonged immobilization, particularly when combined with resistance training. Nonetheless, definitive evidence of isolated systemic action is lacking. Future studies should employ rigorous experimental designs isolating WBV to clarify its therapeutic potential as a standalone modality.